Does a Major Earthquake Change Job Preferences and Human Values?. Issue 3 (27th April 2017) - Oishi, Shigehiro; Yagi, Ayano; Komiya, Asuka; Kohlbacher, Florian; Kusumi, Takashi; Ishii, Keiko
Abstract: Does a major natural disaster change human values and job preferences? The present studies examined whether the experience of a natural disaster experience shifts people's values and job preferences toward pro‐social directions. In Study 1 (cross‐temporal analysis), we analysed job application data in nine cities in Japan over 12 years and found that the popularity of pro‐social occupations (e.g. firefighter) increased after the Great Hanshin–Awaji Earthquake in 1995, in particular the area hit hardest by the quake. In Study 2 (a large national survey), we found that Japanese respondents who had experienced a major earthquake are more likely to hold a pro‐social job than those who never experienced a major earthquake. Together, the current findings suggest that the experience of a major natural disaster shifts human values from the egocentric to the allocentric direction, which in turn could result in a social structure that values pro‐social occupations. Copyright © 2017 European Association of Personality Psychology